2010
DOI: 10.1097/qai.0b013e3181ba4536
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction of Ritonavir-Boosted Elvitegravir and Maraviroc

Abstract: During elvitegravir/r plus maraviroc administration, no elvitegravir or ritonavir dose change and a reduced 150-mg dose of maraviroc are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Maraviroc was approved based on the MOTIVATE trials comprised of 85% individuals with European ancestry (Gulick et al, 2008) and most previous maraviroc pharmacokinetic studies were conducted in participants with European ancestry, with the median percentage of participants with European ancestry at 78.5% (Abel et al, 2008a,b,c,d,f;Chan et al, 2008;Pozniak et al, 2008;Dumond et al, 2009;Andrews et al, 2010;Ramanathan et al, 2010;Brown et al, 2011;Kakuda et al, 2011;Gruber et al, 2013;Mora-Peris et al, 2013;Taiwo et al, 2013;Vourvahis et al, 2013). A few studies compared maraviroc concentrations in individuals with African ancestry with individuals with European ancestry and concluded that there were no differences or higher concentrations in individuals with African ancestry (FDA, 2007;Okoli et al, 2012), which may be due to the use of CYP3A inhibitors such as ritonavir in the optimized background therapy in which CYP3A5 activity may have been inhibited in individuals who are carrying CYP3A5*1 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Maraviroc was approved based on the MOTIVATE trials comprised of 85% individuals with European ancestry (Gulick et al, 2008) and most previous maraviroc pharmacokinetic studies were conducted in participants with European ancestry, with the median percentage of participants with European ancestry at 78.5% (Abel et al, 2008a,b,c,d,f;Chan et al, 2008;Pozniak et al, 2008;Dumond et al, 2009;Andrews et al, 2010;Ramanathan et al, 2010;Brown et al, 2011;Kakuda et al, 2011;Gruber et al, 2013;Mora-Peris et al, 2013;Taiwo et al, 2013;Vourvahis et al, 2013). A few studies compared maraviroc concentrations in individuals with African ancestry with individuals with European ancestry and concluded that there were no differences or higher concentrations in individuals with African ancestry (FDA, 2007;Okoli et al, 2012), which may be due to the use of CYP3A inhibitors such as ritonavir in the optimized background therapy in which CYP3A5 activity may have been inhibited in individuals who are carrying CYP3A5*1 allele.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the clinical observation that the pharmacoenhancement effect of RTV results from inhibition of CYP3A and that it persists beyond the time that the plasma concentrations of RTV are adequately above or close to K i values conferring direct inhibition of the enzymes. [13][14][15] Besides affecting the PKs of HIV PI drugs, RTV has been shown in clinical studies to enhance the PKs of important antiviral drugs that are CYP3A substrates, including the HIV-1 integrase inhibitor elvitegravir, 16 the CCR5 antagonist maraviroc, 17,18 and the HCV PI narlaprevir. 19 Elvitegravir is metabolized primarily by CYP3A4 in the liver and intestine.…”
mentioning
confidence: 99%
“…A minimum sample size of 12 subjects per cohort was planned to provide 90% confidence intervals (CI) for the difference between the treatments on the natural log scale for AUC , C max , and C of Ϯ0.0722, Ϯ0.1705, and Ϯ0.0582, respectively, for MVC; Ϯ0.1049, Ϯ0.1116, and Ϯ0.2542, respectively, for APV; and Ϯ0.079, Ϯ0.1541, and Ϯ0.1723, respectively, for RTV, with 80% coverage probability. These precision values were calculated by using the Clinical Biostatistics Executable Tool (Pfizer, Inc., New York, NY) and assumed the estimated intrasubject standard deviations of natural log AUC , C max , and C to be 0.119, (19). To allow for any subjects who might not complete the study, 14 subjects were recruited for each cohort.…”
Section: Methodsmentioning
confidence: 99%